2007
DOI: 10.1071/wf06101
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the effects of landscape fuel treatments on fire growth and behaviour in a Mediterranean landscape (eastern Spain)

Abstract: The number of large fires increased in the 1970s in the Valencia region (eastern Spain), as in most northern Mediterranean countries, owing to the fuel accumulation that affected large areas as a consequence of an intensive land abandonment. The Ayora site (Valencia province) was affected by a large fire in July 1979. We parameterised the fire growth model FARSITE for the 1979 fire conditions using remote sensing-derived fuel cartography. We simulated different fuel scenarios to study the interactions between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
2
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 14 publications
3
59
2
5
Order By: Relevance
“…This can be explained by several factors, namely the lower priority given for fire fighting in shrublands (on the assumption that they are the least valuable land cover), the number of human-caused ignitions (e.g. burning for rangeland management purposes, such as creating pastures) and the higher rate of fire spread in this LULC (Duguy et al, 2007;Fernandes, 2009;Moreira et al, 2009). Additionally, as a consequence of shallower soils that prevent dense forest to establish (Garcia-Fayos et al, 1998) and abandonment of hard to mechanize terrace cultivation (Tatoni et al, 1994), shrublands are a common land cover type in steeper slopes where the rate of fire spread is higher.…”
Section: Land Cover Influences Fire Patternsmentioning
confidence: 99%
See 2 more Smart Citations
“…This can be explained by several factors, namely the lower priority given for fire fighting in shrublands (on the assumption that they are the least valuable land cover), the number of human-caused ignitions (e.g. burning for rangeland management purposes, such as creating pastures) and the higher rate of fire spread in this LULC (Duguy et al, 2007;Fernandes, 2009;Moreira et al, 2009). Additionally, as a consequence of shallower soils that prevent dense forest to establish (Garcia-Fayos et al, 1998) and abandonment of hard to mechanize terrace cultivation (Tatoni et al, 1994), shrublands are a common land cover type in steeper slopes where the rate of fire spread is higher.…”
Section: Land Cover Influences Fire Patternsmentioning
confidence: 99%
“…Other studies applied fire resistance rules to LULC types at the scale of fire events (Viedma et al, 2009) or at both stand and landscape scales (Gonzalez et al, 2005(Gonzalez et al, , 2008 and showed that landscape resistance to fire was negatively influenced by the spatial contiguity of LULC, and positively influenced by the diversity resulting from fuel contrast at fire edges. Simulation models also showed that fire spread and behaviour were greatly influenced by fuel spatial distribution (Duguy et al 2007). …”
Section: Land Cover Influences Fire Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…A FARSITE study conducted by Duguy et al (2007) in the Spanish Mediterranean found firebreaks to be highly effective in the reduction of fire size. The study also suggested that FARSITE was a highly effective model for testing fuel treatments, including firebreaks.…”
Section: Previous Farsite Studiesmentioning
confidence: 99%
“…Fuel treatments are another common and highly effective tool to minimize fire hazard. Fuel treatments are considered to be any kind of change in the spatial arrangement of fuel to retard or cease the propagation of fire (Duguy et al, 2007). Common fuel treatments include the creation of water points, firebreaks, or various techniques of vegetative thinning (Van Wagtendonk, 1996;Stephens, 1998).…”
Section: Previous Farsite Studiesmentioning
confidence: 99%